Growth of a cohort of very low birth weight infants in Johannesburg, South Africa - Cooper Peter A; Ballot Daynia E; Mackay Cheryl A (BMC, 2011)
Abstract Background Little is known about the growth of VLBW infants in South Africa. The aim of this study was to assess the growth of a cohort of VLBW infants in Johannesburg. Methods A secondary analysis of a prospective cohort was conducted on 139 VLBW infants (birth weight ≤1500 g) admitted to Charlotte Maxeke Johannesburg Academic Hospital. Growth measurements were obtained from patient files and compared with the World Health Organization Child Growth Standards (WHO-CGS) and with a previous cohort of South African VLBW infants. The sample size per analysis ranged from 11 to 81 infants. Results Comparison with the WHO-CGS showed initial poor growth followed by gradual catch up growth with mean Z scores of 0.0 at 20 months postmenstrual age for weight, -0.8 at 20 months postmenstrual age for length and 0.0 at 3 months postmenstrual age for head circumference. Growth was comparable with that of a previous cohort of South African VLBW infants in all parameters. Conclusions Initial poor growth in the study sample was followed by gradual catch up growth but with persistent deficits in length for age at 20 months postmenstrual age relative to healthy term infants.